Encontros com o diabo. - Maria Cecilia Marks (RUS (São Paulo), 2015)
The purpose of this article is to analyze, from descriptions of situations and characters, devil's representation in the novels The Brothers Karamazov, by Fyodor Dostoevsky, and Doctor Faustus, by Thomas Mann. The theoretical approach includes concepts developed by Mikhail Bakhtin, such as the carnivalization in literature and cronotopos.